HUBUNGAN JENIS DAN FREKUENSI JAJANAN TERHADAP PENGALAMAN KARIES GIGI PADA ANAK USIA SEKOLAH DI SDN CISALAK III KABUPATEN SUMEDANG - Rifa dwi wahyuni; Yenni Hendriani Praptiwi; Isa Insanuddin; Tiurmina Sirait (Poltekkes Kemenkes Bandung, 2022)
The most common dental and oral disease in the community, especially in school-age children, is dental caries. One of the causes of dental caries is the type and frequency of cardiogenic snacks. This study aims to determine the relationship between the type and frequency of snacks on the experience of dental caries in school-age children at SDN Cisalak III, Sumedang Regency. This type of research is quantitative analytic with cross-sectional. Samples were taken by purposive sampling method with inclusion and exclusion criteria. Measurement of the type and frequency of snacks was carried out using a questionnaire filled out by students aged 12 years. The experience of dental caries was measured directly by the DMF-t index, design with fisher exact hypothesis test. The results of this study indicate that the type of snacks consumed the most is the type of cardiogenic snacks as much as 64.1% with a high frequency of cardiogenic snacks at 74.4%. From the results of direct examination, it was found that the DMF-T index of respondents had very high criteria, namely 51.3%. After the Fisher exact test, there was a significant relationship between the type of snacks and the experience of dental caries P(0.02) < (0.05) and there was a significant relationship between the frequency of snacks and the experience of dental caries in school-age children P(0.04) < (0.05).